Enhancing the Permeate Flux of Direct Contact Membrane Distillation Modules with Inserting 3D Printing Turbulence Promoters - Chang, Hsuan (Membranes (Basel), 2021)
Two geometric shape turbulence promoters (circular and square of same areas) of different array patterns using three-dimensional (3D) printing technology were designed for direct contact membrane distillation (DCMD) modules in the present study. The DCMD device was performed at middle temperature operation (about 45 °C to 60 °C) of hot inlet saline water associated with a constant temperature of inlet cold stream. Attempts to reduce the disadvantageous temperature polarization effect were made inserting the 3D turbulence promoters to promote both the mass and heat transfer characteristics in improving pure water productivity. The additive manufacturing 3D turbulence promoters acting as eddy promoters could not only strengthen the membrane stability by preventing vibration but also enhance the permeate flux with lessening temperature polarization effect. Therefore, the 3D turbulence promoters were individually inserted into the flow channel of the DCMD device to create vortices in the flow stream and increase turbulent intensity. The modeling equations for predicting the permeate flux in DCMD modules by inserting the manufacturing 3D turbulence promoter were investigated theoretically and experimentally. The effects of the operating conditions under various geometric shapes and array patterns of turbulence promoters on the permeate flux with hot inlet saline temperatures and flow rates as parameters were studied. The distributions of the fluid velocities were examined using computational fluid dynamics (CFD). Experimental study has demonstrated a great potential to significantly accomplish permeate flux enhancement in such new design of the DCMD system. The permeate flux enhancement for the DCMD module by inserting 3D turbulence promoters in the flow channel could provide a maximum relative increment of up to 61.7% as compared to that in the empty channel device. The temperature polarization coefficient ([Formula: see text]) was found in this study for various geometric shapes and flow patterns. A larger [Formula: see text] value (the less thermal resistance) was achieved in the countercurrent-flow operation than that in the concurrent-flow operation. An optimal design of the module with inserting turbulence promoters was also delineated when considering both permeate flux enhancement and energy utilization effectiveness.